ESTRUS INDUCTION RESPONSE FOLLOWING HORMONE TREATMENT IN MURRAH BUFFALO - DHALKARI, S; SAHATPURE, S K; PATIL, A D; PATI, P; GAWANDE, A P (The Indian Journal of Animal Reproduction, 2022)
Eighteen anestrus Murrah buffalo were divided equally into three different groups comprising of 6 buffalo each. One group received norgestomet ear implant for 7 days along with norgestomet and estradiol valerate (i.m.) on day 0. Another group received inj. buserelin acetate (i.m.) on day 0 along with a progesterone impregnated intravaginal insert for 7 days. The remaining buffalo were kept as untreated control. Norgestomet-based and intravaginal progesterone-based treatment led to estrus induction in 50% and 83.3% buffalo, respectively. However, there was no difference (p>0.05) in time required for onset of estrus and duration of induced estrus between treatment groups. The intensity of estrus was better in intravaginal progesterone-treated buffalo. In summary, intravaginal progesterone-based treatment had an edge over norgestomet ear implant treatment for induction of estrus in anestrus Murrah buffalo.